The phytopathogen Dickeya dadantii 3937 cpxR locus gene participates in the regulation of virulence and the global c‐di‐GMP network. (23rd April 2022) - Jiang, Daqing; Zeng, Quan; Banerjee, Biswarup; Lin, Haiping; Srok, John; Yu, Manda; Yang, Ching‐Hong
Abstract: Bacteria use signal transduction systems to sense and respond to their external environment. The two‐component system CpxA/CpxR senses misfolded envelope protein stress and responds by up‐regulating envelope protein factors and down‐regulating virulence factors in several animal pathogens. Dickeya dadantii is a phytopathogen equipped with a type III secretion system (T3SS) for manipulating the host immune response. We found that deletion of cpxR enhanced the expression of the T3SS marker gene hrpA in a designated T3SS‐inducing minimal medium (MM). In the ∆ cpxR mutant, multiple T3SS and c‐di‐GMP regulators were also up‐regulated. Subsequent analysis revealed that deletion of the phosphodiesterase gene egcpB in ∆ cpxR abolished the enhanced T3SS expression. This suggested that CpxR suppresses EGcpB levels, causing low T3SS expression in MM. Furthermore, we found that the ∆ cpxR mutant displayed low c‐di‐GMP phenotypes in biofilm formation and swimming. Increased production of cellular c‐di‐GMP by in trans expression of the diguanylate cyclase gene gcpA was negated in the ∆ cpxR mutant. Here, we propose that CpxA/CpxR regulates T3SS expression by manipulating the c‐di‐GMP network, in turn modifying the multiple physiological activities involved in the response to environmental stresses in D. dadantii . Abstract : The stress response regulator CpxR modulates T3SS expression and multiple physiological activities by manipulating the c‐di‐GMP network in the phytopathogen Dickeya dadantii .